بنیادی انسانی حقوق:اسلامی ومغربی قوانین کے تناظر میں: Fundamental Human Rights: In the context of Islamic and Western laws - Sahib Din; Hafiz Muhammad Adil (AL-IDRAK JOURNAL, 2023)
Islam is the bearer of admiration for humanity and constitutional rights. Islam's philosophy of human rights is different from other religions. Islam teaches us moderation in life. He gave such a comprehensive concept of human rights in which there is a mutual balance between rights and duties. Hazrat Muhammad Mustafa ﷺ has given such golden teachings regarding every aspect of human life which can create beauty and balance in life. Guarantees. The foundation of human rights in Islam is based on monotheistic thought and thought. Islam considers human rights as a necessity for human dignity and respect, because according to the religious theory, man is the successor of Allah on earth and in this sense is worthy of honor and respect. In the Islamic society, every individual deserves respect and freedom regardless of religion or nationality. Islam has rejected all kinds of gender, race, and class privileges in the provision of human rights. Likewise, all the above-mentioned rights in the international agreement After the Second World War, a consensus was created in the Universal Declaration of Human Rights about all human rights, which are the basic rights of every human being and should be provided to every human being without discrimination.